Keadilan Organisasi dan Pengaruhnya Terhadap Komitmen Organisasi Pegawai DISKOPUKM dan DISDUKCAPIL Kabupaten Sleman - Arifah, Rina Nur; Subiyanto, Didik (LPPM Institut Bisnis dan Informatika Kesatuan, 2021)
This study aims to determine organizational justice and itseffect on organizational commitment in the Office of Small and Medium Enterprises Cooperatives of Sleman Regency and the Department of Population and Civil Registry of Sleman Regency.The sample used in this study amounted to 50 respondents. The sampling method using saturated sampling. The data analysis method used is quantitative analysis using validity and reliability tests, classical assumption tests, multiple regression analysis, t test, and the coefficient of determination. By using the multiple linear regression method, it can be concluded that Y1 = 3,946 + 0.443 X1 + 0.346 X2 + e and Y2 = 16,647 + 0.669 X1 -0.580 X2 + e. The results of simultaneous calculations at Y1 obtained partial test results t count (4.104)> t table (2.011), the significance of the variable distributive justice to the dependent variable, namely affective commitment of 0.000 or less than the alpha value of 0.05. Distributive justice variable has a significant effect on affective commitment or H1 is accepted and H0 is rejected. The procedural justice variable t count (2.452)> t table (2.011) the significance of the procedural justice variable on the dependent variable, namely affective commitment of 0.018 or less than the alpha value of 0.05. In conclusion, the value of t count> t table and the significance of 0.018 <0.05 means that the variable procedural justice has a significant effect on affective commitment or H1 is accepted and H0 is rejected. As for Y2, the simultaneous calculation results obtained by partial test results t count (3.103)> t table (2.011) the significance of distributive justice variables to the dependent variable, namely normative commitment of 0.003 or less than the alpha value of 0.05. In conclusion, the value of t count> t table and significance 0.003 <0.05 means that the variable distributive justice has a significant effect on normative commitment or H1 is accepted and H0 is rejected. The procedural justice variable t count (-2.057) <t table (2.011) the significance of the procedural justice variable on the dependent variable, namely the normative commitment of 0.045 or less than the alpha value of 0.05. In conclusion, the value of t count <t table and the significance of 0.045 <0.05 means that the normative justice variable has a significant effect on normative commitment or H1 is rejected and H0 is rejected. Keywords: distributive justice, procedural justice, affective commitment, and normative commitment